Addressing the Gap between Academics and IT Industry in Nepal - Poudel, Hemanta; Upadhyaya, Sharad (Nepal Journal of Multidisciplinary Research, 2023)
This study addresses the gap between academics and IT industry of Nepal. The research is based on the survey of B.Sc. CSIT students of Tribhuvan University. The survey found that a majority of students are not satisfied with the quality of IT education provided by colleges under the affiliation of Tribhuvan University. The students cited several reasons for their dissatisfaction, including lack of industry-relevant training, real-world exposure, and career counseling. To ensure the sustainability and competitiveness of the sector, it is necessary to bridge the gap. thus, the recommendations in this research can help industry professionals, professors, educators, and policymakers to bridge the gap and meet the needs of the industry.